2018
DOI: 10.1002/mnfr.201700726
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Does Not Play a Functional Role in Adipose Tissue Development in Rodent Models

Abstract: Data indicate that vitamin D does not play a fundamental role in adipogenesis because vitamin D does not affect fetal adipogenesis. Moreover, the smaller adipocytes observed in adult Vdr-KO mice are presumably caused by an increased energy expenditure due to alopecia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The lean phenotype and defective cellular adipogenesis in the VDR -null mice become apparent with age [ 32 ] and reduction in adipocyte size is observed in older (1 year) but not in young (21 days) mice [ 35 ]. Further, maternal vitamin D deficiency does not impact adipose tissue development in offspring [ 35 36 ]. These results indicate that deficiency of VDR does not affect fat deposition during early development.…”
Section: Vitamin D and Adipose Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…The lean phenotype and defective cellular adipogenesis in the VDR -null mice become apparent with age [ 32 ] and reduction in adipocyte size is observed in older (1 year) but not in young (21 days) mice [ 35 ]. Further, maternal vitamin D deficiency does not impact adipose tissue development in offspring [ 35 36 ]. These results indicate that deficiency of VDR does not affect fat deposition during early development.…”
Section: Vitamin D and Adipose Biologymentioning
confidence: 99%
“…These results indicate that deficiency of VDR does not affect fat deposition during early development. Age-associated lean phenotype in the VDR -null mice may be due to the fact that 1,25(OH) 2 D 3 -VDR decreases energy expenditure through uncoupling process [ 13 ] and age-associated alopecia [ 35 ].…”
Section: Vitamin D and Adipose Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent VDR-knockout study report did not support a fundamental role for vitamin D in adipogenesis (Schutkowski et al 2018). While VDR knockouts represent a valuable genetic model of completely obliterated genomic vitamin D activity, these models may not recapitulate the consequences of dietinduced VDD, which better mimic human VDD with loss of both genomic and non-genomic effects, allowing also for potential physiological adaptations to low vitamin D provision (Narvaez et al 2009, Kong et al 2013, Narvaez et al 2013.…”
Section: Adipogenesis and Dohad Effectsmentioning
confidence: 99%
“…To elucidate whether Vdr deficiency was associated with cardiac hypertrophy or impaired cardiac function independently of blood pressure, we assessed heart weight, cardiac myocyte morphology, and heart function via echocardiography. Findings from a previous study that revealed that Vdr –/– mice have an increased energy expenditure due to alopecia were confirmed (Schutkowski et al, 2018). As we did not find any differences in blood pressure, cardiac morphology and heart function between Vdr –/– and Vdr +/+ mice, we assume that vitamin D does not have an independent causal role in cardiac morphology.…”
Section: Discussionmentioning
confidence: 60%